Revalidation of the Brazilian genus Discocyrtanus, with description of two new species (Opiliones: Gonyleptidae: Pachylinae) - Kury, Adriano B.; Carvalho, Rafael N. (Zootaxa, 2016)
The genus Discocyrtanus Roewer, 1929, is herein revalidated from the synonymy of Discocyrtus Holmberg, 1878, to include besides the type species Discocyrtanus goyazius Roewer, 1929, four other Brazilian species, two of them new—Discocyrtanus bugre sp. nov. and Discocyrtanus tocantinensis sp. nov.—and two newly transferred from Discocyrtus: Discocyrtanus oliverioi (H. Soares, 1945) comb. nov., and Discocyrtanus pertenuis (Mello-Leitão, 1935) comb. nov. Three species, Discocyrtus pectinifemur Mello-Leitão, 1937, Discocyrtus fimbriatus Mello-Leitão, 1939, and Discocyrtus canalsi Roewer, 1943, are considered junior subjective synonyms of Discocyrtanus pertenuis comb. nov.. A mix-up between labeling of original illustrations of two species of Discocyrtus described by Mello-Leitão is noted.